PENGARUH TAX AMNESTY, SANKSI PAJAK DAN SOSIALISASI PERPAJAKAN TERHADAP PENERIMAAN PAJAK DI KPP PRATAMA JAKARTA JATINEGARA : The Influence of Tax Amnesty, Tax Sanctions and Tax Socialization on Tax Revenue at KPP Pratama Jakarta Jatinegara - Christin Jevania; Ganda T. Hutapea; Jonson Pakpahan (Fundamental Management Journal, 2023)
Abstract In these studies, the impact of tax amnesty, tax sanctions, and tax socialization on tax revenue in KPP Pratama Jakarta Jatinegara is to be ascertained. Quantitative research methodology is employed in this area of study. All KPP Pratama Jakarta Jatinegara staff and employees who are now employed in the study's populations. Samples strategy employed in these studies is known as purposeful sampling. 31 persons in total took part in the survey. For the purposes of this study, primary data is employed, with respondents' responses serving as the major source of primary data. With the use of SPSS 26, direct linear regressions was use to analyzing data. Research's findings are as follows: Tax Sanctions, with a regression coefficients of 0.938 and a t counts of 21.569, has a positive and significancy impacts on taxes revenue in KPP Pratama Jakarta Jatinegara; Tax Amnesty, with a regression coefficients of -0.141 and a t counts of 1.939, has no positive and insignificant impact on tax revenue; and Tax Socialization, with a regression coefficients of 0.938 and a t counts of 21.569. Keywords: Tax Amnesty, Tax Sanctions, Tax Socialization, Tax Revenue